2005
DOI: 10.1158/1078-0432.ccr-04-1912
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 4 Expression in Colorectal Carcinoma and Its Prognostic Significance

Abstract: Purpose: Metabotropic glutamate receptors (mGluR) play a variety of roles in both neuronal and nonneuronal cells. Recently, we reported that mGluR4 mediates 5-fluorouracil resistance in a human colon cancer cell line. In this study, we evaluated the nonneural expression of mGluR4 and clarified the existence of mGluR4 in normal colon epithelium and colorectal carcinomas. We also investigated the association of mGluR4 expression levels with various clinicopathologic parameters. Experimental Design: mGluR4 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 29 publications
2
110
0
3
Order By: Relevance
“…In addition, strong immunoreactivity for mGluR2/3 was observed in granular cells of the afferent arteriole (Gill & Pulido, 2001), indicating a possible role in the control of renin release, a hormone which belongs to the renin-angiotensin system involved in regulation of electrolyte, fluid balance and blood pressure (Jackson et al, 1985). In human kidney, focal expression of mGluR4 was detected in the collecting duct (Chang et al, 2005), whereas positivity of a normal mouse glomerulus for mGluR7 was found along the glomerular basement membrane (Rastaldi et al, 2006).…”
Section: Other Organs 41 Kidneymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, strong immunoreactivity for mGluR2/3 was observed in granular cells of the afferent arteriole (Gill & Pulido, 2001), indicating a possible role in the control of renin release, a hormone which belongs to the renin-angiotensin system involved in regulation of electrolyte, fluid balance and blood pressure (Jackson et al, 1985). In human kidney, focal expression of mGluR4 was detected in the collecting duct (Chang et al, 2005), whereas positivity of a normal mouse glomerulus for mGluR7 was found along the glomerular basement membrane (Rastaldi et al, 2006).…”
Section: Other Organs 41 Kidneymentioning
confidence: 99%
“…The presence of mGluR2/3 and mGluR1/5 has been demonstrated in neurons of jejunum and ileum, suggesting that they may play a role in the regulation of intestinal motility (Larzabal et al, 1999;Liu & Kirchgessner, 2000;Nasser et al, 2007). On the other hand, mGluR4 and mGluR7 are expressed in colon mucosa (Chang et al, 2005;Julio-Peper et al, 2010). Activation of mGluR7 in the colon could be a component of secretory disorders such as stress-induced diarrhea (Julio-Peper et al, 2010).…”
Section: Liver and Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant glutamate signaling also plays roles in patho-physiological diseases such as chronic pain, depression and anxiety (Swanson, Bures et al 2005). Recently, glutamate signaling has been shown to be involved in various neoplasms including gliomas, colon cancer, breast carcinomas and melanoma (Albasanz, Ros et al 1997;Pollock, Cohen-Solal et al 2003;Chang, Yoo et al 2005). Metabotropic glutamate receptors transduce glutamate induced signaling through the activation of heterotrimeric G-proteins.…”
Section: Melanocortin-1 Receptor (Mc1r)mentioning
confidence: 99%
“…9 Individual mGlu receptors have been detected in cancer cells both inside and outside the CNS. [10][11][12][13] In addition, mGlu receptor subtypes with a long C-terminal domain are endowed with 'constitutive activity', and are therefore active in the absence of extracellular glutamate. 14 These data suggest that mGlu receptors are involved in the regulation of general processes of cell biology that are common to developing cells, cells of peripheral organs, and cancer cells.…”
mentioning
confidence: 99%